Study of HPV16 L1 Capsid Seropositivity in Patients with Oral and Oropharyngeal Cancers - Shalini Kanaparti; Prasanthi Kolli; Pendyala Jyothi; Alapati Yedukondala Rao; Talapagala Lokeshu; Jahnavi Induluri (Wolters Kluwer Medknow Publications, 2021)
Introduction: Epidemiologic studies show that incidence of oral and oropharyngeal cancers (OPCs) is increasing worldwide over the last decades and the increase is more marked in men than in women. Several meta-analyses have suggested a rising prevalence of human papillomavirus (HPV) in the setting of OPC over time and have now reached epidemic proportions in many areas of the world. The aim of the study is to study the seroprevalence of HPV16-specific immunoglobulin (Ig) G and IgM antibodies and to determine whether the presence of these antibodies could be used as a potential biomarker in HPV16-related oral and OPCs. Materials and methods: Blood samples were collected from 70 patients with oral and OPCs. Samples were analyzed by indirect enzyme-linked immunosorbant assay (ELISA) to detect HPV16-specific IgG and IgM antibodies. Furthermore, the association of various other causal factors such as smoking, alcohol consumption, and betel nut chewing were also evaluated. Results: ELISA revealed that the HPV16-specific IgG antibodies were detected in 7 (10%) out of 70 patients analyzed and HPV16-specific IgM antibodies were not detected in all the cases (0%). High prevalence n = 4 (57.1%) of HPV16-related oral and OPCs was observed among males and in the 51 to 60 years age group who were smokers and alcohol abusers. Conclusion: Determining the HPV status in patients with OPC by serology might be an affordable option in the clinical settings to reduce the morbidity and mortality of patients with oral and OPCs by early intervention.